Press group resistance, belief about alcohol consumption and con-sumption in university students - Londoño Perez, Constanza (Anales de Psicología / Annals of Psychology, 2010)
The present study aimed to describe the predictive association between handling the press group resistance and the beliefs about the level of alcohol consumption of a non-representative stratified random sample of 147 university students between 15 and 25 years of both genders. The Audit Test, the Resistance of Press Group Questionnaire and Belief about Consumption Alcohol was used. The results show a significant association between low indirect press group resistance, perceived invulnerability, and the perceived barriers to slow or stop consuming and risky consumption. We discuss the implications of the findings in the development of preven-tion programs targeting this population